Preparation of PVDF/PTFE hollow fiber membranes for direct contact membrane distillation via thermally induced phase separation method - Zhao, Jie (2019)
Polyvinylidene fluoride (PVDF)/polytetrafluoroethylene (PTFE) hollow fiber membranes were developed via thermally induced phase separation (TIPS) method for direct contact membrane distillation (DCMD). The effects of PTFE addition on the thermal behavior of the dope mixtures and membrane formation were investigated. It was found that the crystallization of PVDF was significantly enhanced with increased nucleation sites provided by PTFE particles, leading to promoted formation of smaller spherulites in a greater density. Furthermore, the improved uniformity and increased amount of cavity between the spherical crystallites coherently facilitated the formation of smaller pores ranging from 0.08 to 0.12 μm. With certain PTFE loading, the membranes exhibited improved porosity, water permeability and hydrophobicity as well as enhanced tensile strength of 9.4 ± 0.3 MPa. To examine the DCMD performance, the membranes were tested under various conditions using 3.5 wt% NaCl solution. A stable permeation flux of 28.3 kg m− 2 h− 1 at the feed temperature of 60 °C with 99.99% NaCl rejection for over 50 h of operation was achieved, which is comparable with similar type of PVDF membranes while the newly developed membrane exhibited better mechanical strength. This study suggests that the as-spun PVDF/PTFE hollow fiber membranes have potential for DCMD applications.